A framework for building user oriented maintenance management for national religious secondary schools / Nor Amin Radzuan, Hairul Nizam Mansor and Ashrof Zainuddin - Radzuan, Nor Amin; Mansor, Hairul Nizam; Zainuddin, Ashrof (2018)
The area of building maintenance creates an opportunity for scholar, practitioner, building owner, stake holder, end user and others to participate in various study to establish issues and solution to the problem concerning building maintenance. Building maintenance is not only limited to restore the physical of the building and its facilities but also contribute to improve the existing environment of building user. The paper highlights the significance of building maintenance for National Religious Secondary school to take into consideration buildinguser as one of the main factors in maintenance management frameworks. The proposed framework is developed through unstructured interview with relevant stakeholders that involved in school maintenance with integration of building user and service quality. The objective is to investigate the nature of maintenance management for National Religious Secondary school. A pilot survey was conducted to obtain some overview on the current condition and practice of maintenance management for national religious secondary school in Perak one of the states in Malaysia. Some secondary data were provided by the national religious secondary school maintenance department. The maintenance data were analyzed with reference to the location, building elements and frequency of reported defects that were recorded in a year. The collected building maintenance data show that issues on building maintenance still occur that is equivalent with the age of the school buildings. It indicates that the proposed integration of building user in maintenance management framework will improvise the service rendered by the operator and satisfy the building user.